Studying the Effect of Variables on Acyclovir Microsponge - Noor Y. Fareed; Hanan J. Kassab (College of Pharmacy University of Baghdad, 2018)
The aim of the present investigation was to develop a microsponge delivery system of acyclovir to control its release when applied topically thereby reducing dosing frequency and enhancement patient compliance. The microsponges were produced by the oil in oil emulsion solvent diffusion method. The effect of different formulation and process variables such as internal phase volume, polymer type, drug-polymer ratio, stirring speed and stirring duration on microsponge production yield, loading efficiency, particle size and in-vitro drug release was evaluated. The result showed that the microsponge F2 prepared from Eudrajet RS polymer had optimum physical properties regarding the loading efficiency of 99.71_+ 0.7% and production yield which was 85%. Also, F2 showed 66% drug release within 8 hours. Accordingly, the oil in oil emulsion solvent diffusion method is an effective technique to formulate microsponges with maximum production yield and loading efficiency for acyclovir.